Patriarchal Cultural Perspective in Woman Characters of Hidden Figures Movie - Ida Ayu Panuntun; Imroatul Chusna (Faculty of Language and Literature, University of Surakarta, 2021)
This research used a research object in the form of movie entitled Hidden Figures. The research had more attention in the study of patriarchal culture in woman characters in that film. Patriarchal culture is a culture which focuses in the theory with a feminist approach. That theory emphasizes in the power of stratification and privilege based on gender. This research aimed to describe how patriarchal culture reflected in Hidden Figures movie. The researcher used descriptive qualitative research design in this research. The data of this research was in the form of utterances. Those utterances were utterances delivered among the characters in that movie. In collecting the data, the researcher conducted a library study. In analyzing the data, the researcher used a feminist approach. The researcher found that patriarchal culture which reflected in Hidden Figures Movie was identified into four kinds of patriarchy types. Those were characters, setting, ploting and conflict.